The Effect of Return Expectation, Motivation, Perceived Value of Risk and Technological Progress on Investment Decision in Sharia Peer to Peer Lending - Abdul Manap; Yusmita Hawari; Andriani Lubis; Eddy Sukandar; Arko Pujadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this research is to test and analyze the effect of perceived risk on investment decisions in Islamic peer to peer lending, test and analyze the effect of expected returns on investment decisions in Islamic peer to peer lending, test and analyze behavioral motivation on investment decisions in peer to peer sharia lending, examines and analyzes the effect of technological advances on investment decisions in sharia peer to peer lending and analyzes the simultaneous influence of perceived risk, expected return, behavioral motivation and technological advances on investment decisions in sharia peer to peer lending. This study was concluded that the higher the risk received, the greater the investment decision. This is because the sample of respondents in this study already has sufficient knowledge about investment, where to obtain high returns must be accompanied by high risks as well. In addition, the behavioral motivation variable also influences the investment decision variable significantly. The reason for this could be that the respondents in this study felt more confident if they knew that their company's reputation was good and would have more confidence in the information and recommendations provided by other parties as a basis for making investment decisions.